2021
DOI: 10.3390/cancers13184703
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Role of Aldehyde Dehydrogenases in Prostate Cancer Stem Cells

Abstract: Cancer stem cells (CSCs) are the only tumor cells possessing self-renewal and differentiation properties, making them an engine of tumor progression and a source of tumor regrowth after treatment. Conventional therapies eliminate most non-CSCs, while CSCs often remain radiation and drug resistant, leading to tumor relapse and metastases. Thus, targeting CSCs might be a powerful tool to overcome tumor resistance and increase the efficiency of current cancer treatment strategies. The identification and isolation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 221 publications
3
19
0
Order By: Relevance
“…High expression of ALDH3A2 in the tumor tissue has been shown to be associated with prolonged overall survival in patients with gastric cancer and clear cell renal cell carcinoma ( 35 , 36 ). In prostate cancer, the expression of ALDH3A2 was decreased in the primary cancer tissue compared to the healthy prostate tissue but increased in response to anticancer treatments ( 37 ). Similarly, the expression of ALDH3A2 was downregulated in gastric cancer tissue compared to normal tissue ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…High expression of ALDH3A2 in the tumor tissue has been shown to be associated with prolonged overall survival in patients with gastric cancer and clear cell renal cell carcinoma ( 35 , 36 ). In prostate cancer, the expression of ALDH3A2 was decreased in the primary cancer tissue compared to the healthy prostate tissue but increased in response to anticancer treatments ( 37 ). Similarly, the expression of ALDH3A2 was downregulated in gastric cancer tissue compared to normal tissue ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits aldehyde dehydrogenase (ALDH), resulting in unpleasant accumulation of acetaldehyde if ethanol is consumed. ALDH is a central marker for stemness in both cancer cells and normal cells [143][144][145][146][147][148][149][150]. ALDH might be more properly termed a mediator of stem attributes.…”
Section: Disulfirammentioning
confidence: 99%
“…It has been shown that ALDH high CD44 + PCa cells and the corresponding ALDH low CD44 − PCa cells manifest as PCSCs and non-PCSCs (20). A recent review by Dr. Jakob Püschel et al summarized the roles of different members in ALDH superfamily in PCSCs detailly (18). Among them, ALDH1A1 and ALDH3A1 are the most reported because they play a critical role in maintaining PCSC stemness (18,21,22).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review by Dr. Jakob Püschel et al summarized the roles of different members in ALDH superfamily in PCSCs detailly (18). Among them, ALDH1A1 and ALDH3A1 are the most reported because they play a critical role in maintaining PCSC stemness (18,21,22). On the other hand, Dr. Saketh S. Dinavahi et al give us a detailed review of the latest progress on ALDH inhibitors in cancer therapy (23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation